'Would you like to eat an insect?'—Children's perceptions of and thoughts about eating insects. (22nd September 2020) - Nyberg, Maria; Olsson, Viktoria; Wendin, Karin
Abstract: Interest in eating insects has increased in Western countries; however, substantial challenges exist regarding acceptability and cultural ideas. Researchers have widely studied the acceptance of eating insects, but few studies have focused on children's thoughts. The aim of this study is to explore young children's perceptions about eating insects and how this insight might help understanding of ways to increase the willingness to eat insects. Three focus group interviews were conducted with children aged 4–5 years in a public preschool in Sweden. Each focus group consisted of four to five children; in total 13 (eight girls and five boys) participated. In exploring their perceptions of eating insects, the children were balancing between fantasy and reality, and between curiosity and fear, showing many, sometimes contradictory, emotions and relationships to insects as food. The children expressed a clear normative picture of what was considered food, illustrated by ideas about insects being something that are not allowed to eat. They were also concerned about whether the insect was dead before being eaten. Using children's fantasy and curiosity for new things, experimenting with insect‐based products and ingredients in well‐known dishes and contexts, and discussing different ways of eating them, acceptance of eating insects might increase.